Can sonographic features be efficacy predictors of robotic massage treatment for masseter and temporal muscle in patients with temporomandibular disorder with myofascial pain?. Issue 1 (2nd January 2016) - Ariji, Yoshiko; Nakayama, Miwa; Nishiyama, Wataru; Ogi, Nobumi; Sakuma, Shigemitsu; Katsumata, Akitoshi; Kurita, Kenichi; Ariji, Eiichiro
Abstract: Objective: The aim of this study was to detect sonographic predictors for the efficacy of massage treatment of masseter and temporal muscle in temporomandibular disorders (TMDs) patients with myofascial pain. Methods: Thirty-seven TMD patients with myofascial pain (6 men and 31 women, a median age of 45 years) were enrolled. An oral rehabilitation robot massaged the patient's masseter and temporal muscles with a standard massage pressure of 10 N for 16 min. The standard treatment protocol was set five sessions every 2 weeks. The median total duration of treatment was 9.5 weeks. Efficacy of treatment was evaluated based on maximum mouth opening and visual analog scale scores of muscle pain and daily life impediments. The intramuscular echogenic bands and elasticity index ratios of the masseter muscles were evaluated on sonographic or sonoelastographic images obtained before treatment and after the third and last treatment sessions. Results: The sonographic features detected different changes after the third treatment session between the therapy-effective and therapy-ineffective groups: in the therapy-effective group, the frequency of visibility of the distinct echogenic bands increased, and the elasticity index ratio decreased. Conclusion: Sonographic features after the third treatment session may be useful as predictors of therapeutic efficacy.